The art of floral design - Hunter, Norah T. (Delmar/Cengage Learning, 2013)
This book introduces you to the full range of floral design techniques, from basic to advanced, with vivid photographs, colorful illustrations, and easy-to-understand descriptions. Balancing theory with practice, this edition covers the history of design, artistic elements, floral anatomy, and nomenclature, along with techniques, tools, and specialties. This book prepares you for the real business world with discussions on distribution, marketing, advertising, finance, labor concerns, and the industry-specific issues you need to know for success on the job.